Influence of blood contamination on the bond strength and biointeractivity of Biodentine used as root-end filling - M. Shalabi; S. Saber; T. Elsewify (Elsevier, 2020)
Aim: To evaluate the influence of blood contamination on the bond strength and apatite forming ability of Biodentine used as root-end filling material. Methodology: Eighty (n = 80) extracted single-rooted, sound human maxillary anterior teeth were prepared and obturated. Then, the roots were resected, retrograde cavities were prepared and Biodentine was inserted as the root-end filling material. Teeth were then randomly divided into 2 equal groups (n = 40) according to the setting environment of Biodentine i.e., group A where setting took place in human blood and group B where setting took place in deionized water (control group). Teeth were incubated at 37  °C for 45 min to ensure complete setting. Root discs with the filling material in their core were prepared. Push-out bond strength test was performed using a universal testing machine and failure mode was examined. Both groups were aged in HBSS for 30 days. Apatite nucleation was evaluated at one-day, 7-days, and 30-days interval using SEM for morphological analysis and EDX for elemental analysis. Calculation of the Ca/P ratios was performed in addition to XRD for crystal phase analysis. Results: Blood contamination (group A) resulted in significant reduction of bond strength values. It also affected the amount of apatite deposition on the material surface and interfacial spaces with higher Ca/P ratios than that of the normal stoichiometric hydroxyapatite. Conclusions: Blood contamination during setting of Biodentine had a detrimental effect on the bond strength and reduced the nucleation of apatite in comparison to non-contaminated group.